Electric-Magnetic Duality in Gravity and Higher-Spin Fields - Danehkar, Ashkbiz (Frontiers in Physics, 2019)
Over the past two decades, electric-magnetic duality has made significant progress in linearized gravity and higher spin gauge fields in arbitrary dimensions. By analogy with Maxwell theory, the Dirac quantization condition has been generalized to both the conserved electric-type and magnetic-type sources associated with gravitational fields and higher spin fields. The linearized Einstein equations in D dimensions, which are expressed in terms of the Pauli-Fierz field of the graviton described by a 2nd-rank symmetric tensor, can be dual to the linearized field equations of the dual graviton described by a Young symmetry (D − 3, 1) tensor. Hence, the dual formulations of linearized gravity are written by a 2nd-rank symmetric tensor describing the Pauli-Fierz field of the dual graviton in D = 4, while we have the Curtright field with Young symmetry type (2, 1) in D = 5. The equations of motion of spin-s fields (s > 2) described by the generalized Fronsdal action can also be dualized to the equations of motion of dual spin-s fields. In this review, we focus on dual formulations of gravity and higher spin fields in the linearized theory, and study their SO(2) electric-magnetic duality invariance, twisted self-duality conditions, harmonic conditions for wave solutions, and their configurations with electric-type and magnetic-type sources. Furthermore, we briefly discuss the latest developments in their interacting theories.